Modal shift to inland waterways: dealing with barriers in two Swedish cases. Issue 2 (3rd March 2020) - Rogerson, Sara; Santén, Vendela; Svanberg, Martin; Williamsson, Jon; Woxenius, Johan
ABSTRACT: This paper analyses strategies to overcome barriers to a modal shift to inland waterway transport (IWT). Barriers identified in research literature have been categorised as regulatory, financial, service quality and market characteristics. Using two cases involving Swedish entrepreneurs initiating IWT, this paper has shown how barriers to the modal shift to IWT can be managed where markets are limited. Modal shift involves multiple actors, and the entrepreneurs interacted with ports, shippers, shipping companies, regulatory actors, forwarders and hauliers, depending on the barrier. Strategies to manage barriers included negotiating, educating stakeholders, securing volumes, conducting a proof-of-concept run and identifying business opportunities for stakeholders. The findings can increase stakeholders' knowledge of IWT. Policy makers aiming to promote modal shift must understand that fees and legislation act as barriers.